The effect of job embeddedness on turnover intention with organizational commitment as a mediating variable - Latifatul Khoirun Nisa'; Ayu Lucy Larassaty (Jurnal Mantik, 2024)
The objectives in this study are 1) to analyze job embeddedness variables on organizational commitment, 2) to analyze variables on turnover intention, 3) to analyze organizational commitment variables on turnover intention, 4) to analyze job embeddedness variables on turnover intention mediated by organizational commitment. This research uses a quantitative approach with a population of employees of PT Trikayarasa Jaya Food. The sampling technique in this study used purposive sampling. The sample used was employees of the production and stripping section totaling 70. The reason for sampling in the production and stripping section is that the target is not met. This study uses a questionnaire data collection method and data collection instruments using a Likert scale. The data analysis technique in this study uses part analysis using SmartPLS software version 4.0. The results of this study found that job embeddedness affects organizational commitment, job embeddedness has no effect on turnover intention, organizational commitment affects turnover intention, job embeddedness mediated by organizational commitment affects turnover intention